Development of Learning Tools Based on the Culturally Responsive Transformative Teaching Model with a Socio-Scientific Issues Approach: Evaluation of Validity and Practicality - Arifin, Ahmad Aris; Ramdani, Agus; Andayani, Yayuk (Postgraduate, University of Mataram, 2024)
The importance of conducting this research is based on observations indicating that the implementation of the Kurikulum Merdeka on the theme of local wisdom has been limited to Sabtu Budaya (Cultural Saturday) activities, without further integration into the learning process, particularly in the development of learning tools. This research aims to develop a learning tool based on the CRTT model with a SSI approach that is both valid and practical. The type of research employed is Research and Development (R&D), with a 4D development design limited to the define, design, and develop stages. The development stage is restricted to validation and practicality testing. Data collection techniques included expert validation sheets, student and teacher response questionnaires, and observation sheets for the implementation of learning activities. Data analysis techniques used Aiken's V validity index, Percentage of Agreement, and percentage method. The results of the content and construct validity tests indicate that the learning tool based on the CRTT model with the SSI approach is classified as highly valid, with the assessment agreement among validators being reliable. The results of the practicality test show that student responses had an average of 89.02%, categorized as practical, teacher responses were 92.81%, categorized as practical, and the implementation of learning activities reached 85.71%. These results indicate that the learning tool based on the CRTT model with the SSI approach is both valid and practical for use in the learning process.